Concrete Experiences and Support Needs Regarding the Euthanasia Practice in Adults With Psychiatric Conditions: A Qualitative Interview Study Among Healthcare Professionals and Volunteers in Belgium - Verhofstadt, Monica; Audenaert, Kurt; Mortier, Freddy; Deliens, Luc; Liégeois, Axel; Pardon, Koen; Chambaere, Kenneth (Frontiers in Psychiatry, 2022)
Objective Although euthanasia in the context of adult psychiatry is legalised in Belgium, it poses major ethical and clinical challenges for the health care professionals and volunteers involved. This study aimed to address these members’ concrete experiences and support needs. Methods A qualitative semi-structured interview study was conducted with 16 physicians and 14 other health care professionals and volunteers, with at least one concrete experience with euthanasia requests and procedures concerning adults with psychiatric conditions. Findings Concrete experiences concerned the following 8 domains: (1) the impact of euthanasia on the clinical trajectory and (2) on the therapeutic relationship, (3) internal and (4) external collaborative partnerships, (5) patients’ social inner circle (non-)involvement, (6) the use of recently published guidelines and, (7) the first criminal trials on this topic, and (8) the act of euthanasia. The following 8 main support needs emerged; (1) protocols addressing specific sub-populations and pathologies, (2) protocols specifically drawn up for non-medics, (3) guidance on how to adequately implement the two-track approach, (4) (after)care for patients, (5) (after)care for the health care team, (6) guidance on the patient’s social inner circle involvement, (7) enhanced education measures, and (8) enhanced financial measures, including incentives for holistic, palliative care approaches. Conclusion The health care professionals and volunteers reported many positive and negative experiences in dealing with euthanasia requests in adult psychiatry. They reported several support needs across the extensive euthanasia trajectory, pertaining to concrete management of thorny issues that guidelines do not (yet) touch on. Important implications of our study relate to tackling these existing issues, and to paying sufficient attention to the impact of a euthanasia trajectory on all actors, including the patients and their social inner circle, involved.